Analysis and Simulation of SELR Model in Exploring and Predicting the Dynamics of Independent Curriculum in Addressing the Gap in Student Achievement in City Centers and Remote Areas in South Sulawesi - Muktamar, Muhammad Ilham; Syam, Rahmat; Side, Syafruddin; Sainon Andi Pandjajangi, Andi Muhammad Ridho Yusuf (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
This study aims to build and analyze the SELR mathematical model in the context of the Independent Curriculum, in order to explore and predict the gap in student achievement between urban and remote areas in South Sulawesi. This study combines theoretical studies and applications by conducting simulations using Maple software. The study population involved 400 students from urban areas and 400 students from remote areas where simulation data was used to predict the dynamics of adaptation to the Independent Curriculum. The results showed that the Independent Curriculum was not fully effective in addressing the achievement gap, with a low basic reproduction number (R₀), both in urban and remote areas. The R₀ value of 0.204 in urban areas and 0.614 in remote areas indicates that the spread of curriculum adaptation is still limited and cannot create a significant impact on improving student achievement. This study indicates the need for additional adjustments and interventions in the implementation of the Independent Curriculum to achieve more equitable and inclusive results in various regions .